O impacto da implantação do Modelo de Excelência da Gestão® (MEG) no desempenho organizacional das empresas reconhecidas no prêmio mineiro da qualidade - Christiane de Miranda e Silva Correia (2016)
In order to achieve strategic results, organizations look for increasing of competitiveness and survival with the implementation of management models that support process improvements and also satisfy the needs of stakeholders. This thesis presents the main contributions of organizational performance, management models and quality awards in Brazil and worldwide. We present the history and management models requirements adopted in major quality awards. The model analyzed in this work is the Modelo de Excelência da Gestão® (MEG) which is a systemic model adopted by numerous Brazilian organizations. This model is based on essential fundamentals to achieve the performance excellence. We sought to identify how was the evolution and impact on organizational performance with the implementation of the Modelo de Excelência da Gestão® and recognition in Prêmio Mineiro da Qualidade. This work adopts the approach to qualitative research and describes with Case Study the intervention and context in real life of the model management implementation impact and the recognition in organizational performance, especially towards to the stakeholders. It was conducted a census with a questionnaire sent to all recognized organizations from 2003 to 2015, and in the second phase were conducted unstructured interviews with organizations and stakeholders and collection of secondary data. With the analyses of the survey data, we evidence that the implementation of MEG and participation in PMQ contributes to achieve results and thus satisfy the needs of stakeholders. In general, stakeholders confirm that there was an impact on the results and perceived with changes and improvements implemented in organizations. The implementation of management model occurred at the same time with other management methodologies such as ISO 9001 and Balanced Scorecard which also contributed to the achievement of organizational performance.